ANALISIS STRATEGI KOMUNIKASI PEMASARAN RADIO PELITAKASIH DALAM UPAYA MENARIK MINAT PENGIKLAN DI ERAINDUSTRI 4.0 - REYNALDI RENOANANTYO, (2020)
Abstract This study discusses efforts to attract advertisers' interest in radio in the 4.0 era through marketing communication strategies adopted by Pelita Kasih radio, considering the declining number of listeners that radio has the challenge of maintaining its presence in the eyes of advertisers. This is what made researchers interested in finding out about the strategy adopted by Radio Pelita Kasih, because based on the marketing team's report in 2019 the value of advertising spending increased. In this study researchers through qualitative methods conducted in-depth interviews with several informants, namely general manager, program manager, marketing manager. This shows that Radio Pelita Kasih's efforts in attracting advertisers' interest through 6 promotional efforts are factors namely advertising, personal selling, sales promotion, direct selling, public relations, internet marketing by using IMC integrated marketing communication in this radio marketing system. Through this research, researchers know the forms of strategies carried out from various elements of integrated marketing communication as well as forms of multimediality efforts related to the 4.0 era, mutually supporting and cooperating with one another, because all are interrelated and inseparable. The implementation of an integrated marketing communication strategy is run optimally even with various obstacles and challenges of limited human resources, so there needs to be attention in order to improve the quality of optimal human resources. Keywords : marketing communication strategy, radio station.